FINANCIAL PERFORMANCE INFORMATION SYSTEM AT THE ANDROID-BASED DIRA JAYA SINAR RESKI COOPERATIVE - Sartika; Ridwansyah, Ridwansyah; Haripuddin, Haripuddin (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to find out the results of the design and testing results of ISO 25010 on the application of financial performance information system in the Android-based Dira Jaya Sinar Reski cooperative. This research uses a type of R&D (Research and Development) that uses a waterfall development model. The data collection techniques used are interviews, observations, documentation, and questionnaires/questionnaires. Based on the results of the research, a Financial Performance Information System was developed at the Android-Based Dira Jaya Sinar Reski Cooperative which has been tested using ISO 25010 testing using 4 aspects of testing including functional suitability, usability, performance efficiency, and portability. The final result of the overall assessment is that the financial performance information system in the Dira Jaya Sinar Reski cooperative based on android can be accepted to be used as a medium that makes it easier for the admin of the Dira Jaya Sinar Reski cooperative in Takalar Regency in managing financial data on savings and loans in the Dira Jaya Sinar Reski cooperative in Takalar Regency.